RGS12 represses oral squamous cell carcinoma by driving M1 polarization of tumor-associated macrophages via controlling ciliary MYCBP2/KIF2A signaling - Gongsheng Yuan; Shuting Yang; Shuying Yang (Nature Publishing Group, 2023)
Abstract Tumor-associated macrophages (TAMs) play crucial roles in tumor progression and immune responses. However, mechanisms of driving TAMs to antitumor function remain unknown. Here, transcriptome profiling analysis of human oral cancer tissues indicated that regulator of G protein signaling 12 (RGS12) regulates pathologic processes and immune-related pathways. Mice with RGS12 knockout in macrophages displayed decreased M1 TAMs in oral cancer tissues, and extensive proliferation and invasion of oral cancer cells. RGS12 increased the M1 macrophages with features of increased ciliated cell number and cilia length. Mechanistically, RGS12 associates with and activates MYC binding protein 2 (MYCBP2) to degrade the cilia protein kinesin family member 2A (KIF2A) in TAMs. Our results demonstrate that RGS12 is an essential oral cancer biomarker and regulator for immunosuppressive TAMs activation.